Authentication, phytochemical characterization and anti-bacterial activity of two Artemisia species. (15th December 2020) - Yang, Meng-Ting; Kuo, Tien-Fen; Chung, Kuo-Fang; Liang, Yu-Chuan; Yang, Chu-Wen; Lin, Chih-Yu; Feng, Ching-Shan; Chen, Zeng-Weng; Lee, Tsung-Han; Hsiao, Chiao-Ling; Yang, Wen-Chin
Highlights: Molecular and chemotaxonomic approaches are combined for plant authentication. These approaches assist the morphological authentication of A. indica and A. argyi . Six phytochemicals of the Artemisia species were identified. Artemisia plants and their phytochemicals inhibit food-borne harmful bacteria. This inhibition is via destruction of the bacterial membrane. Abstract: Artemisia species are aromatic herbs used as food and/or ethnomedicine worldwide; however, the use of these plants is often impeded by misidentification. Here, molecular and chemotaxonomic approaches were combined to assist in the morphology-based authentication of Artemisia species, and Artemisia indica and Artemisia argyi were identified. The plant extracts and compounds obtained from these species, 1, 8-cineole, carveol, α-elemene, α-farnesene, methyl linolenate, diisooctyl phthalate inhibited the growth of food-borne harmful bacteria. Mechanistic studies showed that the extract and active compounds of A. indica killed Gram-negative and -positive bacteria via destruction of the bacterial membrane. Finally, in vivo data demonstrated that A. indica protected against bacterial infection in mice as evidenced by survival rate, bacterial load in organs, gut pathology, diarrhea, body weight, food consumption, stool weight, and pathology score. A. indica and its active compounds have potential for use as food supplements for food-borne bacterial diseases and thus improve human health.